Using Dirt to Clean Dirt: Deconstructing The Enigmatic Portrait of Mara in Darko’s Beyond The Horizon - Sanka, Confidence Gbolo; Issaka, Charity Azumi; Abrafi, Josephine Adu; Yeboah, Philomena Abaka (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
Mara’s travails in Ghana and subsequently Germany, have provided the fertile grounds for critics to draw various labels for the protagonist in Beyond the horizon. To some readers, Mara is a victim who has been exploited through patriarchy; to others, Mara learns from her environment and finally asserts her independence; and to a third group of critics, Mara is complicit in the fate that befalls her. Thus Mara remains an enigma, earning our sympathy or losing it; winning our admiration or courting our disgust depending on which angle we look at her. This paper does an objective analysis of Mara by resorting to the theory of deconstruction which helps us unearth more than what meets the eye in the novel. This approach helps us provide answers to issues such as how Mara is presented in the narrative, the motivations that guide her actions and inactions and how Mara, as an individual, and the society at large contribute in creating the protagonist we part ways with at the end of the narrative. The conclusion arrived at is that there are myriads of relationships among the characters in the narrative that provide hierarchies of meaning which can be deconstructed to produce more subtle and valid ones. Mara is not simply a victim; she is complicit, to some extent, and she takes steps to obliterate those she considers the vermin of the earth. In short, she uses dirt (prostitution) to clean dirt (patriarchy, male chauvinism, discrimination, poverty, racism).KEY WORDS: deconstruction, dirt, Ghana, marriage, patriarchy, prostitution.